2023
DOI: 10.2147/ijgm.s406926
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Rheumatoid Arthritis and Atrial Fibrillation: Epidemiology, Pathophysiology and Management

Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia with a significant increase in morbidity and mortality worldwide. Rheumatoid arthritis (RA), as a systemic inflammatory disease, affecting 0.5–1.0% of the adult population, is associated with increased incidence of cardiac arrhythmias such as AF. Several epidemiologic studies find that the risk of AF is increased in RA when compared with the general population. Other studies are inconsistent. Considering that inflammation plays an important role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 128 publications
(160 reference statements)
0
2
0
1
Order By: Relevance
“…( Current findings suggest that rheumatoid arthritis can cause atrial remodeling and induce the development and maintenance of AF (85). Accordingly, some scholars found that resveratrol can reverse rheumatoid arthritis-induced atrial structural and metabolic remodeling, then slow down the development of AF (86).…”
Section: Chinese Herbs Model Intervention Cellular and Molecular Mech...mentioning
confidence: 99%
See 1 more Smart Citation
“…( Current findings suggest that rheumatoid arthritis can cause atrial remodeling and induce the development and maintenance of AF (85). Accordingly, some scholars found that resveratrol can reverse rheumatoid arthritis-induced atrial structural and metabolic remodeling, then slow down the development of AF (86).…”
Section: Chinese Herbs Model Intervention Cellular and Molecular Mech...mentioning
confidence: 99%
“…Zhong et al evaluated the therapeutic effect of resveratrol in reducing the occurrence of AF in a heart failure model and explored the underlying mechanisms, finding that myocardial fibrosis was significantly reduced in the resveratrol group, ion channels including Kv1.4, Kv1.5, KvLQT1, Kir2.1, and Nav1.5 were significantly upregulated, and PI3K, AKT, and eNOS mRNA and protein expression were also significantly enhanced ( 84 ). Current findings suggest that rheumatoid arthritis can cause atrial remodeling and induce the development and maintenance of AF ( 85 ). Accordingly, some scholars found that resveratrol can reverse rheumatoid arthritis-induced atrial structural and metabolic remodeling, then slow down the development of AF ( 86 ).…”
Section: Chinese Herbal Medicines With Preventive and Curative Effect...mentioning
confidence: 99%
“…Фибрилляция предсердий (ФП) является наиболее распространённой сердечной аритмией со значительным увеличением заболеваемости и смертности во всем мире. В литературе имеются указания, что РА ассоциирован с повышенной частотой сердечных аритмий, таких как ФП [36]. В датском общенациональном когортном исследовании было показано, что частота ФП у пациентов с РА на 40% выше, чем в общей популяции [37].…”
Section: фибрилляция предсердийunclassified